Hubungan Fasilitas dengan Motivasi Belajar Peserta Didik di TPA Suhron Raja Enda - Amzal, Amzal; Solfema, Solfema (Inovan Publisher, 2025)
The purpose of this study is to examine the relationship between learning facilities and student motivation at the Suhron Raja Enda Jorong Lubuk Gadang Quran Learning Center in West Pasaman Regency. This research is a quantitative correlation study. The research population consists of 30 students in the Juz'amma and Al-Qur'an classes at TPA Suhron Raja Enda, with a sample of 15 students selected randomly using a guided questionnaire/survey in the form of a list of questions. The study found a significant relationship between learning facilities and student learning motivation at TPA Suhron Raja Enda Jorong Lubuk Gadang, West Pasaman Regency. It can therefore be concluded that there is a significant relationship between learning facilities and student learning motivation at TPA Suhron Raja Enda Jorong Lubuk Gadang, West Pasaman Regency. If the learning facilities for students are complete, it will lead to high learning motivation among students. Conversely, if the available facilities are incomplete, it will lead to low learning motivation among students at TPA Suhron Raja Enda Jorong Lubuk Gadang, Pasaman Barat Regency.